AN IMPLEMENTATION OF LOCATION-AWARE MULTIMEDIA INFORMATION DOWNLOAD TO MOBILE SYSTEM - TSE, PHILIP K. C.; LAM, W.K.; NG, K.W.; CHAN, CHRISTOPHER (Journal of Mobile Multimedia, 2005)
Current mobile devices can capture and receive multimedia objects via the network operators. There are not many application systems that handle multimedia objects existing in both computers and mobile devices. We have successfully developed an application system to directly deliver multimedia objects from computers at local exhibition booths to the multimedia-enabled mobile phones. In this paper, we describe our target application as the location-aware multimedia information system in an exhibition centre. We have used different techniques including file stripping, proxy delivery, image preprocessing, transcoding, and Bluetooth protocol in this system.